THE EFFECT OF BETA-CAROTENE INTAKE ON THE ENZYMES GPX AND CAT AND THE OFFENSIVE PERFORMANCE OF ADVANCED BOXERS - Abd Ali Hamza, Dr. Haidar; Qasim Kadhim, Ahmed (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Boxing training is characterized by high intensity similar to the nature of fight performance, and this causes large accumulations in the levels of lactate salts in the muscle, as well as the appearance of free radicals in the blood, which in turn cause damage and may cause oxidative stress to the boxers, which causes inflammation in the joints and muscles as a result of the intensity of the exercise and fight. Hence, the study aimed to study The research included that the individuals in the research sample take doses of beta-carotene Forest 1.5 mg, 500 IU, in doses specified by the nutritionist for the purpose of stimulating the enzymes responsible for oxidizing electrolytes and free radicals in the blood of advanced boxers at the Hindiyah Sports Club. The researchers used the two-group experimental approach. The research sample was represented by advanced boxing players at the Hindi Club in Karbala Governorate, who numbered 14 light and medium weight boxers. They were given doses of beta-carotene under the supervision of a specialist doctor, one dose per day (capsule) three hours before training and for 30 days after that, and post-tests were conducted. GOT-CAT enzyme, as well as endurance to offensive performance (straight, side, and upward punches (gouging)). The researchers used the SPSS statistical program to extract the research results, and from them they concluded that beta-carotene antioxidants clearly contributed to reducing the severity of free radicals and their oxidation through high levels of the GOT enzyme. -CAT, as well as its role in raising the level of boxers’ endurance in throwing punches. In light of this, the researchers recommend the need to focus on taking antioxidants and proper nutrition for boxers and other sports, under the supervision of a nutritionist.